The WebQuest as accessible strategy in social studies subject - Gina Aracely García Cedeño, Marcos Alejandro Yánez Rodríguez (International Journal of Advanced Science and Technology, 2020)
The objective of this work has been to present a technological and educational resource, to work on the subject of social studies, such as it is the WebQuest, aimed at the students of the tenth grade of Basic General Education of the Fiscal Education Unit Simón Bolívar, located in Ecuador. The WebQuest is a research oriented that helps the teacher to make proper use of the Internet in the classroom; In addition to being accessible, it promotes self-employment and is based on cooperative and collaborative learning. It was proposed to use the templates offered by the tool Google Sites, also, the social network WhatsApp to share the link of the Site to the class group, due to the evidence found from the academic documents reviewed, the use of this strategy is of great benefit so that students are motivated and appropriate of the knowledge provided by the teacher.